Study the effect of circular hole on dynamic fracture properties of cracked PMMA specimen under impact loads. (October 2021) - Wang, Lei; Zhu, Zheming; Zhou, Lei; Gao, Weiting; Dong, Yuqing; Niu, Caoyuan; Ai, Ting
Highlights: The influence mechanism of the circular hole on crack propagation behaviour was studied. The cause for the turning point during crack propagation was analyzed using AUTODYN software. The effect of the circular hole on the dynamic propagation toughness (DPT) was measured. The dynamic fracture toughness versus crack speeds were analyzed. Abstract: Hole defects and crack defects usually coexist in a real engineering rock masses, they together affect the structural security of rock masses. With the purpose of investigating the effect of circular hole on crack initiation and propagation process under dynamic loads, a circular opening specimen with straight crack cavity (COSSCC) model was proposed in this study and polymethyl methacrylate was chosen to make the specimens. A series of dynamic experiments were carried out utilizing a drop hammer impact test system (DHITS), crack speeds and crack initiation time were determined utilizing crack propagation gauge (CPG). The maximum principal stress field evolution in the crack evolution process was simulated using a modified finite element difference method software, and dynamic fracture toughness was calculated by a traditional finite element method software. Some significantly conclusions can be obtained: As the inclination angle θ of the circular hole is less than 10 o, crack propagation trajectories will propagate to the surface of the circular hole; As the inclination angle θ of circular hole is 20 o and 30 o, crack propagation trajectories will turn in the direction of circular hole but not reach the circular hole; As circular hole inclination angle θ is 40 o and 50 o, the crack shows a pure mode I crack propagation. As crack propagates near the circular hole, crack propagation speeds increase significantly. The dynamic propagation toughness during crack propagation is not constant and is less than dynamic initiation toughness (DIT) and the dynamic propagate toughness (DPT) is inversely proportional to the crack speeds.